Industrial Welfare: an organ of progressive ideas in dealing with personnel. . Industrial Welfare and Personnel Management. Industrial Welfare Society
(1952) titled: Industrial Welfare and Personnel Management. Industrial Welfare Society. Ed.: Thomas Fassam.